Rule of law in war international law and United States counterinsurgency in Iraq and Afghanistan - McLeod, Travers 1982- (Oxford University Press, 2015)
This book places international law at the centre of the transformation of United States counterinsurgency (COIN) that occurred during the Iraq and Afghanistan wars. It claims international law matters more than is often assumed and more than we have previously been able to claim, contradicting existing theoretical assumptions. In particular, the book contends international law matters in a case that may be regarded as particularly tough for international law, that is, the development of a key military doctrine, the execution of that doctrine on the battlefield, and the ultimate conduct of armed conflict. To do so, the book traces international law's influence in the construction of modern U.S. COIN doctrine, specifically, Field Manual 3-24, Counterinsurgency, released by the U.S. Army and Marine Corps in December 2006. It then assesses how international law's doctrinal interaction held up in Iraq and Afghanistan. The account of this doctrinal change is based on extensive access to the primary actors and materials, including FM 3-24's drafting history, field documents, and interviews with military officers of various ranks who have served multiple deployments in Iraq and Afghanistan.